急性硬膜外血しゅ除去術決行の限界 Ｉ 神経学的所見からの検討 - KOMATSU Shinro; SATO Tomohiko; OGAWA Akira; WADA Tokuo; ONUMA Takehide (Japanese Journal of National Medical Services, 1982)
In this study we examined the correlations between neurological findings before surgery and prognosis in 24 cases with acute epidural hematoma. There was a good correlation between the state of consciousness before surgery and prognosis. Patients with a consciousness level of semi-coma at the time of admission had a good prognosis, however patients with coma at the time of admission had a poor prognosis. In 8 cases with coma at the time of operation, 4 of those cases with semicoma at the time of admission had good prognosis. On the other hand, two cases with bilateral mydriasis died.We also described the limitation of surgical treatment based on these results. 急性硬膜外血腫24例の術前の神経学的所見と予後との関係を検討し, 更にこの結果を参考に血腫除去術決行の限界について考察した. その結果, 術前の意識レベルから見た血腫除去術決行可能な限界は, 3-3-9度方式で意識200付近までの症例と考えられた. しかしこのうち, 入院時意識が既に200の症例では生命予後のみならず機能予後も極めて悪く手術適応はほとんど無いが, 入院時意識が100までであれば例えその後意識が悪化し200の段階になつても, 可及的速やかな血腫除去術により良好な予後が期待でき, 手術適応があると考えられた. 一方, 術前の対光反射及び瞳孔散大の有無と予後との間の検討では, 対光反射の有無と予後との間にはあまり明確な相関関係はないが, 両側瞳孔散大例はいずれも死亡例であり, 生命予後からみた急性硬膜外血腫除去術決行の限界を示唆する所見と考えられた.